Address in Portuguese and Spanish: Studies in diachrony and diachronic reconstruction - Hummel, Martin (2020)
The volume Address in Portuguese and Spanish: Studies in Diachrony and Diachronic Reconstruction provides the first systematic contrastive approach to the history of forms of address in Portuguese and Spanish in their European and American varieties. From a methodological point of view, the volume is innovative as it links historical linguistics with diachronic reconstruction based on synchronic variation. It includes theoretical reflections as well as fine-grained empirical studies.